2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037378
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cognitive fatigue using EEG parameters

Abstract: Continuous and repetitive performance of a task is likely to induce a drop in alertness levels of an individual. Changes in Electroencephalogram (EEG) have been proposed in literature as a marker of alertness during repeated performance of a cognitive task set. The present paper investigates the increase in fatigue levels and resultant drop in alertness of subjects during continuous performance of cognitive tasks by analyzing changes in energy of EEG frequency bands. The trends reflected in the EEG parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…There have been many studies that have used the ratio of the EEG rhythm energy: ( α + θ )/ β , α / β , ( α + θ )/( α + β ), θ / β , etc. as indicators of human fatigue [ 52 54 ], and have indicated that their parameters are all statistically significant for fatigue state analysis [ 55 ]. De Waard and Brookhuis [ 52 ] found that the relative energy parameter ( α + θ )/ β decreased with a decrease in alertness level.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…There have been many studies that have used the ratio of the EEG rhythm energy: ( α + θ )/ β , α / β , ( α + θ )/( α + β ), θ / β , etc. as indicators of human fatigue [ 52 54 ], and have indicated that their parameters are all statistically significant for fatigue state analysis [ 55 ]. De Waard and Brookhuis [ 52 ] found that the relative energy parameter ( α + θ )/ β decreased with a decrease in alertness level.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Studies have shown that the EEG signal is decomposed into 4 bands: delta (δ) (0.5-4 Hz), theta (θ) (4-8 Hz), alpha (α) (8-14 Hz), and beta (β) (14-30 Hz) bands, and these can be measured to detect the current mental state [38]. When the subjects were fatigued, the decreased arousal level elevated the delta power [39].…”
Section: Objective Fatigue Analysismentioning
confidence: 99%
“…For this research, fatigue will be de ned as "a sensation of tiredness, often accompanied by alterations in behaviour or performance, which can arise from sustained performance in a cognitively or physically demanding task" [19][20][21]. In addition to self-reported metrics and performance changes, adult BCI studies have identi ed electroencephalography (EEG) biomarkers of fatigue [22,23] most notably increases in alpha band power [24,25].…”
Section: Introductionmentioning
confidence: 99%